2021
DOI: 10.1186/s12887-021-02715-y
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in opioid use for adolescents at US emergency departments

Abstract: Background Racial/ethnic disparities in the use of opioids to treat pain disorders have been previously reported in the emergency department (ED). Further research is needed to better evaluate the impact race/ethnicity may have on the use of opioids in adolescents for the management of pain disorders in the ED. Methods This was a cross-sectional study using data from the National Hospital Ambulatory Medical Care Survey from 2006 to 2016. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The race/ethnicity results are consistent with prior findings that Black and Hispanic people have less opioid misuse than White people (Jones et al, 2015; Martins et al, 2017; Schuler et al, 2021; Vaughn et al, 2016). This may be in part due to racial and ethnic inequities in opioid prescribing or treatment of pain (Hoffman et al, 2016; Lee et al, 2019; Phan et al, 2021; Schuler et al, 2021). In addition, previous literature has consistently found that opioid misuse is associated with lower socioeconomic status within the United States (Dahlman et al, 2021; Han et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The race/ethnicity results are consistent with prior findings that Black and Hispanic people have less opioid misuse than White people (Jones et al, 2015; Martins et al, 2017; Schuler et al, 2021; Vaughn et al, 2016). This may be in part due to racial and ethnic inequities in opioid prescribing or treatment of pain (Hoffman et al, 2016; Lee et al, 2019; Phan et al, 2021; Schuler et al, 2021). In addition, previous literature has consistently found that opioid misuse is associated with lower socioeconomic status within the United States (Dahlman et al, 2021; Han et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors documented are multiple, ranging from genetic influences [10][11][12][13]; personality risk factors, such as impulsivity or the tendency toward risky behavior [14], including use of other substances; traumatic experiences, including early life adversity and family history of substance use disorders [15,16]; demographic characteristics, including exposure to opioids at young age and being male [17,18]; subjective experiences at first opioid use, such as euphoria [19]; nonmedical opioid use, including the use of opioids to get high, improve sleep, decrease anxiety [20]; medical and psychiatric comorbidities, particularly pain conditions or incidence of other substance use disorders [21]; surgical procedures, either minor or major [22,23]; higher and prolonged doses of opioids used [21]. diagnosis, prevention, and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Access to primary care, treatment in the emergency department, and hospital treatment have all been found to have racial discrepancies, with Black children most commonly ending up with less care and poorer quality of care. 2 In the emergency department, patient race can affect analgesia, triage scores, wait times, treatments, diagnostic procedure utilization, rates of patients leaving without being seen, and patient experiences. 3…”
mentioning
confidence: 99%
“…Opioid treatment of pain in adolescents has been found to favor treating non-Hispanic White patients over minorities. A study by Phan et al 2 demonstrated variability in treating pain based on race for the same diagnoses. These trends persist into adulthood, with pain in the Black population being ignored or undertreated across fields and through the end of life.…”
mentioning
confidence: 99%